2009
DOI: 10.7863/jum.2009.28.11.1481
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of Congenital Variations of the Extracranial Vertebral Artery and Assessment of Its Circulation

Abstract: Certain children with a history of recurrent signs of vertigo, headache, and syncope were found to be afflicted with congenital variations of the extracranial vertebral artery. Sonography not only revealed the morphologic variations of the extracranial vertebral artery but also allowed an assessment of changes in blood flow such that posterior circulation ischemia could be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Anatomical variation of the cerebral circulation is common, with an incomplete circle of Willis reported in about 50 % of the population, usually involving at least one absent or hypoplastic communicating artery [47]. Congenital variations in the VA have also been described [48]. These variations are associated with asymmetrical flow [49] and in patients with severe ICA stenosis, a risk of stroke and transient ischemic attack is also present [50].…”
Section: Posture and The Cerebral Circulationmentioning
confidence: 99%
“…Anatomical variation of the cerebral circulation is common, with an incomplete circle of Willis reported in about 50 % of the population, usually involving at least one absent or hypoplastic communicating artery [47]. Congenital variations in the VA have also been described [48]. These variations are associated with asymmetrical flow [49] and in patients with severe ICA stenosis, a risk of stroke and transient ischemic attack is also present [50].…”
Section: Posture and The Cerebral Circulationmentioning
confidence: 99%
“…Additional reports suggested that children with congenital hypoplastic vertebral artery were more susceptible to arteriosclerosis either at a young age or later in adulthood [9,14,22]. …”
Section: Cohort Studies Further Test and Support The Hypothesismentioning
confidence: 99%
“…Decreased vertebral artery diameter has been associated with both reduced blood flow and inadequate blood supply to the posterior circulation in a sonographic evaluation of pediatric patients with a history of headache, vertigo or syncope [9]. The role of VAH in the pathogenesis of migraine has also been examined with color Doppler ultrasound in 59 patients with migraine.…”
Section: Imaging Studies Illustrate That Neurological Symptoms In Submentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most diseases related to vertebrobasilar circulation, such as occlusion, stenosis, and congenital variations of the vertebral artery, have been diagnosed with Doppler sonography in previous studies 5 7 . The spectral Doppler waveform of the vertebral artery has also proven useful for predicting the degree of ipsilateral subclavian artery stenosis and determining whether blood flow is ante‐grade or retrograde 1 , 8 .…”
mentioning
confidence: 99%